EXPERIMENTAL DETERMINATION OF HUMAN ERYTHROCYTE MEMBRANE PERMEABILITY COEFFICIENTS FOR A SERIES OF AMIDES - Gordiyenko, Olga; Gordiyenko, Yuliya; Linnik, Tamara; Gordiyenko, Evgen (c/o Royal Veterinary Colledge, London, 2005)
Erythrocyte membrane permeability coefficients have been determined for a series of amides by a method based on the physical and mathematical modelling of hypotonic haemolysis process. The results show that penetration of the substances occurs by two alternative ways – through aqueous pores formed by proteins and by the direct dissolving of the molecules in membrane lipids. This conclusion can be confirmed by the correlation analysis between permeability coefficients of native erythrocytes and those pre-incubated with the monosodium salt of p-chloromercuribenzenesulfonic acid (pCMBS), and the partition coefficients of the substances in hydrophilic-hydrophobic phases. Penetration of substances through hydrophilic channels is limited by the sterical factor and diameter in particular. Permeability coefficients for erythrocytes pre-incubated with pCMBS increase in an accordance with the rise of the partition coefficients with correlation coefficient of 0.94, thereby indicating a lipid route of permeation of molecules through erythrocyte membranes.
Keywords: Human erythrocyte; Permeability coefficients; Amides